PRIMARY ANGIOSARCOMA OF THE BREAST: A CASE REPORT - Živković, Ognjen; Milićević, Andjela; Inić, Zorka; Kozomara, Zoran; Buta, Marko (HEALTH CARE, 2025)
Background/Aim: Breast angiosarcoma is a rare tumour of vascular endothelium origin, accounting for less than 0.05% of all breast malignancies. The aim of this case report was to point out the importance of early recognition and a multidisciplinary approach in the diagnosis and treatment of this rare entity.Case report: A 44-year-old woman presented for a clinical examination due to a tumour in her right breast. After a mammographic examination, which verified a highly suspicious lobular change at the junction of the upper quadrant of the right breast with a diameter of 86 x 98 mm, a biopsy with a core needle was performed, followed by a radical mastectomy. Pathohistologically, a vascular mesenchymal tumor was verified. Using the immunohistochemical staining method, the tumor showed immunoreactivity to Vimentin, CD31, CD34, and Factor VIII, while AE1/AE3, EMA, estrogen, progesterone, and HER2 were negative, and the diagnosis of poorly differentiated primary angiosarcoma was made.Conclusion: Primary breast angiosarcoma represents a real diagnostic challenge. Due to the tumor's rarity and aggressiveness, a multidisciplinary approach to diagnosis and treatment is essential. Because of the nonspecific clinical and radiographic features of primary angiosarcoma, differential diagnoses encompass both benign and malignant breast conditions. Therefore, histopathological analysis is crucial for accurate diagnosis.
Keywords: Breast angiosarcoma, Immunohistochemistry, Mesenchymal tumours, Primary angiosarcoma